A 40-43-Gb 16 demultiplexer in SiGe technology. - Ong, A. (IEEE Journal of solid state circuits)
A fully integrated OC-768 clock and data recovery IC with SFI-5 1:16 demultiplexer is designed in a 120-GHz/100-GHz (fT/fMAX) SiGe technology. The 16 2.5-Gb/s outputs and additional deskew channel are compliant with the Serdes Framer Implementation Agreement Level 5 specification. The measured bit-error rate is <10-15. The measured jitter tolerance exceeds the mask specified in G.8251. The IC operates with 1.8-V and -5.2-V supplies and dissipates 7.5 W.